The TLR9 Agonist Cobitolimod Induces IL10-Producing Wound Healing Macrophages and Regulatory T Cells in Ulcerative Colitis. (20th October 2019) - Schmitt, Heike; Ulmschneider, Julia; Billmeier, Ulrike; Vieth, Michael; Scarozza, Patrizio; Sonnewald, Sophia; Reid, Stephen; Atreya, Imke; Rath, Timo; Zundler, Sebastian; Langheinrich, Melanie; Schüttler, Jürgen; et al.
Abstract: Background and Aims: The topically applied Toll-like receptor 9 [TLR9] agonist cobitolimod is a first-in-class DNA-based oligonucleotide with demonstrated therapeutic efficacy in clinical trials with ulcerative colitis [UC] patients. We here characterized its anti-inflammatory mechanism in UC. Methods: Luminal cobitolimod administration was evaluated in an experimental dextran sodium sulfate [DSS]-induced colitis model. Cultured blood and mucosal cells from UC patients were treated with cobitolimod and analysed via microarray, quantitative real-time PCR, ELISA and flow cytometry. Intestinal slides of cobitolimod-treated UC patients were analysed by immunohistochemistry. Results: Cobitolimod administration markedly suppressed experimental colitis activity, and microarray analyses demonstrated mucosal IL10 upregulation and suppression of IL17 signalling pathways. Cobitolimod treatment was associated with significant induction of mucosal IL10+Tr1 and Treg cells and suppression of Th17 cells. TLR9 knockout mice indicated that cobitolimod requires TLR9 signalling for IL10 induction. In UC patients, mucosal TLR9 levels correlated with severity of inflammation. Cobitolimod inhibited IL17A and IL17F, but increased IL10 and FoxP3 expression in cultured intestinal UC T cells. Cobitolimod-mediated suppression of intestinal IL17+T cells was abrogated by IL10 blockade. Furthermore, cobitolimod led to heightened IL10 production by wound healing macrophages. Immunohistochemistry in intestinal biopsies of cobitolimod-treated UC patients indicated increased presence of IL10+mononuclear and regulatory T cells, as well as reduction of IL17+cells. Conclusion: Activation of TLR9 via cobitolimod might represent a novel therapeutic approach in UC, as it suppresses Th17 cells and induces anti-inflammatory IL10+macrophages and regulatory T cells, thereby modifying the dysregulated intestinal cytokine balance. Podcast: This article has an associated podcast which can be accessed at https://academic.oup.com/ecco-jcc/pages/podcast